Introduction [in African food systems transformation and the post-Malabo agenda] - Ulimwengu, John M.; Kwofie, Ebenezer M.; Collins, Julia; Yamdjeu, Augustin Wambo (AKADEMIYA2063, 2023)
This year marks 20 years of implementing the Comprehensive Africa Agriculture Development Programme (CAADP), which was launched with the Maputo Declaration in 2003. With CAADP, African leaders committed to promoting agricultural growth as a key catalyst of broader economic development. After the first decade of CAADP implementation, characterized by strong agricultural and economic growth across the continent, the CAADP agenda was broadened under the 2014 Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. The Malabo Declaration reaffirmed the commitments of African heads of state to the original CAADP targets of achieving a 6 percent agricultural growth rate and a 10 percent agricultural expenditure share, while adding further commitments to be achieved by 2025 in areas including nutrition, poverty, resilience, and trade.